1997
DOI: 10.1007/s002130050448
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of chlordiazepoxide on aggressive behavior in male mice: the influence of social factors

Abstract: The present study examined the influence of prior social experience on the effects of chlordiazepoxide (CDP; 5.0, 10.0 and 20.0 mg/kg) on intrasexual aggression in male mice. Prior to drug testing, animals were either individually housed or screened in dyadic encounters in a neutral cage. This novel method yielded four experimental groups comprising animals with different social experiences and different aggressive/defensive characteristics: 1) individually-housed males (I): 2) aggressive males (A); 3) counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 40 publications
5
32
1
Order By: Relevance
“…Previous reports demonstrated that anxiolytic drugs affected aggressive behaviors [4,14,16], and aggression is known to occur in association with anxiety. For example, dominant mice, i.e., those from aggressive strains or winners in social confrontations, also have high anxiety levels [3,5,10]. In the present study we found that the latency to the first attack bite was longer in the EW.…”
supporting
confidence: 51%
“…Previous reports demonstrated that anxiolytic drugs affected aggressive behaviors [4,14,16], and aggression is known to occur in association with anxiety. For example, dominant mice, i.e., those from aggressive strains or winners in social confrontations, also have high anxiety levels [3,5,10]. In the present study we found that the latency to the first attack bite was longer in the EW.…”
supporting
confidence: 51%
“…One of the aims of this study was to establish whether or not the effects of the two drugs in question differed between adolescent and adult mice, as social deprivation in early stages of development may also have profound consequences on adult social behavior [Ferrari et al, 1997]. Therefore, we studied behavioral changes induced by a 15-day isolation period in both adolescent and adult mice; a period that obviously initiates at a different time in each age group.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the prototypic BZ, chlordiazepoxide, increases aggression in male rats toward opponents, an effect that has been replicated in male mice and in lactating mice (Miczek 1974;Rodgers and Waters 1985;Weerts et al 1992;Palanza et al 1996;Ferrari et al 1997). Chlordiazepoxide prolongs aggressive encounters between male rats and increases threat displays and aggressive vocalizations in squirrel monkeys (Miczek 1974;Beck and Cooper 1986;Weerts and Miczek 1996).…”
Section: Introductionmentioning
confidence: 93%